Detection and classification of Mango Leaf diseases utilizing convolutional neural network models - Ferdous, Md.Rubaiat; Amin, Abdulla Al; Shaily, Senjuti Sarkar; Ricky, Fabliha Tarannum; Tabeeb, Tahmeed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.